2019
DOI: 10.1186/s13601-018-0239-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic associations of the response to inhaled corticosteroids in asthma: a systematic review

Abstract: There is wide variability in the response to inhaled corticosteroids (ICS) in asthma. While some of this heterogeneity of response is due to adherence and environmental causes, genetic variation also influences response to treatment and genetic markers may help guide treatment. Over the past years, researchers have investigated the relationship between a large number of genetic variations and response to ICS by performing pharmacogenomic studies. In this systematic review we will provide a summary of recent ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 81 publications
(144 reference statements)
0
47
0
1
Order By: Relevance
“…32,36,40,73,74,79 During this period, candidate-gene studies reported the association of genes previously described in pharmacogenetic studies of pediatric asthma with treatment response (ADRB2, GSDMB, FCER2, and VEGFA). 13,[16][17][18] Additionally, other candidate genes have been related for the first time to this phenotype in children (SPATS2L, ASB3, IL1RL1, MMP9, and COL2A1). Although several findings support previous evidence of some of these genes in asthma treatment response, inconsistent results across the literature or even across the studies included in this review have been found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32,36,40,73,74,79 During this period, candidate-gene studies reported the association of genes previously described in pharmacogenetic studies of pediatric asthma with treatment response (ADRB2, GSDMB, FCER2, and VEGFA). 13,[16][17][18] Additionally, other candidate genes have been related for the first time to this phenotype in children (SPATS2L, ASB3, IL1RL1, MMP9, and COL2A1). Although several findings support previous evidence of some of these genes in asthma treatment response, inconsistent results across the literature or even across the studies included in this review have been found.…”
Section: Discussionmentioning
confidence: 99%
“…2 Corticosteroids contribute to control asthma symptoms due to its anti-inflammatory and immunosuppressive effects as a result of the interaction with the glucocorticoid receptor (GR). 45 Nonetheless, many factors such as an incorrect inhaler technique, 46 a poor adherence, 47 comorbidities, 48 lung microbiome dysbiosis, [49][50][51][52] and genetic variants, 13,17 may contribute to a loss in asthma control and to the development of asthma exacerbations despite ICScontained therapies. The identification of these factors is essential to differentiate children with difficult-to-treat asthma from those that are resistant to pharmacological therapies.…”
Section: Inhaled Corticosteroids (Ics)mentioning
confidence: 99%
See 1 more Smart Citation
“…Erb-B2 tyrosine kinase 2 (ErbB2) was found to be highly correlated with asthma and was suggested to be a novel therapeutic target for asthma [27,28]. Moreover, both NR3C1 and COL1A1 were linked to inflammation in asthmatic airways [29,30]. While, clinical studies have reported that NR3C1 is strongly associated with asthma severity [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the last year, the role of different omics in asthma treatment response has been recapitulated in different reviews [16][17][18][19][20][21]. This review aims to provide an update on the latest findings in omic studies of pediatric asthma treatment response.…”
Section: Introductionmentioning
confidence: 99%